Marga Richter - Mirchandani, Sharon (Women composers (Urbana, Ill.), 2012)
This book offers an introduction to the life and works of significant American composer Marga Richter (born 1926), who has written more than one hundred works for orchestra, chamber ensemble, dance, opera, voice, chorus, piano, organ, and harpsichord. Actively composing into her eighties, Richter is particularly known for her large-scale works performed by ensembles such as the London Philharmonic Orchestra and the Civic Orchestra of Chicago and for other pieces performed by prominent artists including pianist Menahem Pressler, conductor Izler Solomon, and violinist Daniel Heifetz. Interspersing consideration of Richter's musical works with discussion of her life, her musical style, and the origins and performances of her works, the biographer documents a successful composer's professional and private life throughout the twentieth century. Covering Richter's formative years, her influences, and the phases of her career from the 1950s to the present, this book closely examines Richter's many interesting, attractive musical works that draw inspiration from distinctly American, Irish, English, and Asian sources. Drawing extensively on interviews with the composer, the biographer also provides detailed descriptions of Richter's scores and uses reviews and other secondary sources to provide contexts for her work, including their relationship to modern dance, to other musical styles, and to 1970s feminism.